Sarcopenia, severe anxiety and increased C-reactive protein are associated with severe fatigue in patients with inflammatory bowel diseases - Laura Tasson (Nature Portfolio, 2021)
Abstract Patients with inflammatory bowel disease (IBD) report fatigue more frequently than healthy population, but the precise mechanisms underlying its presence are unknown. This study aimed to evaluate the prevalence of fatigue in IBD and its relation with potential causative factors. A survey on fatigue, depression, anxiety, sleep disorders, and the presence of sarcopenia and malnutrition, was sent by email to 244 IBD outpatients of the Gastroenterology Unit of Academic Hospital of Padua. Demographics and clinical data, including the levels of fecal calprotectin (FC) and C-reactive protein (CRP), and current pharmacological treatments were obtained from patients’ medical records. Ninety-nine (40.5%) subjects answered the survey. Ninety-two (92.9%) patients reported fatigue, with sixty-six having mild to moderate fatigue and twenty-six severe fatigue. Multivariate analysis showed that abnormal values of CRP (OR 5.1), severe anxiety (OR 3.7) and sarcopenia (OR 4.4) were the factors independently associated with severe fatigue. Fatigue has a high prevalence in subject affected by IBD. Subjects with altered CRP, sarcopenia and severe anxiety appear more at risk of severe fatigue.